2007
DOI: 10.4049/jimmunol.178.7.4538
|View full text |Cite
|
Sign up to set email alerts
|

Active Suppression of the Pulmonary Immune Response by Francisella tularensis Schu4

Abstract: Francisella tularensis is an obligate, intracellular bacterium that causes acute, lethal disease following inhalation. As an intracellular pathogen F. tularensis must invade cells, replicate, and disseminate while evading host immune responses. The mechanisms by which virulent type A strains of Francisella tularensis accomplish this evasion are not understood. Francisella tularensis has been shown to target multiple cell types in the lung following aerosol infection, including dendritic cells (DC) and macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
260
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(287 citation statements)
references
References 43 publications
25
260
2
Order By: Relevance
“…3 and data not shown). We along with others have observed induction of antiinflammatory cytokines and type I IFN by F. tularensis following infection of antigen-presenting cells (7,8,26,51). As expected, DCs responded to E. coli LPS by secreting IL-12, TNF-␣, IL-1␤, and TGF-␤ into culture supernatant (Fig.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…3 and data not shown). We along with others have observed induction of antiinflammatory cytokines and type I IFN by F. tularensis following infection of antigen-presenting cells (7,8,26,51). As expected, DCs responded to E. coli LPS by secreting IL-12, TNF-␣, IL-1␤, and TGF-␤ into culture supernatant (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Thus, the profound suppression mediated by F. tularensis in DCs was not obtained at the cost of an initial burst of cytokines that might alert the immune system. Importantly, the broad suppression of DC responsiveness (in terms of cytokine secretion) is similar to that observed in the lungs of mice following aerosol infection with Schu S4 (7). Together, these data suggested that Schu S4 suppresses the host immune response in a global sense; that is, interference with host responsiveness is not restricted to infected cells but extends to uninfected cells that may aid in the resolution of infection.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Being an intracellular pathogen, Francisella can survive and replicate in a variety of cell types including macrophages. F. tularensis has been shown to modulate macrophage functions and suppress proinflammatory cytokines (5)(6)(7)(8). The virulence properties and mechanisms underlying innate immune subversion of F. tularensis are unique and remain largely undefined.…”
mentioning
confidence: 99%